2007
DOI: 10.1007/s11128-007-0059-0
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Algorithms Based on the 3-bit Majority

Abstract: Algorithmic cooling is a potentially important technique for making scalable NMR quantum computation feasible in practice. Given the constraints imposed by this approach to quantum computing, the most likely cooling algorithms to be practicable are those based on simple reversible polarization compression (RPC) operations acting locally on small numbers of bits. Several different algorithms using 2-and 3-bit RPC operations have appeared in the literature, and these are the algorithms I consider in this note. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The original idea of algorithmic cooling was developed by Schulman and Vazirani in [25] which uses a technique for Schumacher's quantum data compression [26,27]. Later it was proposed to use a heat-bath to enhance the cooling beyond the compression bounds [23,28].…”
Section: Strong Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original idea of algorithmic cooling was developed by Schulman and Vazirani in [25] which uses a technique for Schumacher's quantum data compression [26,27]. Later it was proposed to use a heat-bath to enhance the cooling beyond the compression bounds [23,28].…”
Section: Strong Interactionmentioning
confidence: 99%
“…The idea is that after the entropy transfer, the heat-bath refreshes the hot qubits and then the entropy transfer can be repeated. Different iterative methods were developed based on this idea [27,29,30]. All of these methods are referred to as "Heat-Bath Algorithmic Cooling".…”
Section: Strong Interactionmentioning
confidence: 99%
“…Based on this work, many cooling algorithms have been designed [6][7][8][9][10][11]. HBAC is not only of theoretical interest, experiments have already demonstrated an improvement in polarization using this protocol with a few qubits [12][13][14][15][16][17][18], where a few rounds of HBAC were reached; and some studies have even included the impact of noise [19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this work, many cooling algorithms have been designed [6][7][8][9][10][11]. HBAC is not only of theoretical interest, experiments have already demonstrated an improvement in polarization using this protocol with a few qubits [12][13][14][15][16][17][18], where a few rounds of HBAC were reached; and some studies have even included the impact of noise [19].Through numerical simulations, Moussa [7] and Schulman et al [8] observed that if the polarization of the bath ( b ) is much smaller than 2 −n , where n is the number of qubits used, the asymptotic polarization reached will be ∼ 2 n−2 b ; but when b is greater than 2 −n , a polarization of order one can be reached. Inspired also by the work of Patange [20], who investigated the use of algorithmic cooling on spins bigger than 1 2 (using NV center where the defect has an effective spin 1), we investigate the case of cooling a qubit using a general spin l, and extra qubits which get contact with a bath.…”
mentioning
confidence: 99%
“…The optimal algorithms, the PPA and all-bonacci, need about half the spins (more precisely, J +2 spins) in order to cool (asymptotically) the coldest spin to 2 J ; we thus see that mPAC is semi-optimal in the sense that it needs twice as much spins to reach nearly the same optimal bias. Section III discusses simple variants of the Fibonacci algorithm: δ-Fibonacci [21,23], and mFib, which fixes the number of cycles at each recursive level. Section IV compares the new algorithms, mPAC and mFib, to previous cooling algorithms, including the PPA, Fibonacci, allbonacci, and PAC algorithms.…”
Section: Rpc Reversible Polarization Compressionmentioning
confidence: 99%